THU0203 Equal Retention and Drug Survival Between Females and Males Requiring Biologic Therapy for Rheumatoid Arthritis. (23rd January 2014) - Lee, J.; Mason, R.; Martin, L.; Barnabe, C.
Abstract : Background: Sex differences in RA prevalence, disease activity levels, and patient-reported outcomes are documented, but no studies have documented drug retention or drug-survival differences. Objectives: To determine retention and drug-survival duration on first and subsequent biologic agents by sex. Methods: Data source: Alberta Biologics Pharmacovigilance Program (ABioPharm), a population-based longitudinal registry. Analysis: Comparison of disease activity measures by sex over the treatment course, drug retention on the first and subsequent biologic agents, number of treatment switches required and drug survival using Kaplan-Meier survival curves. Results: 572 patients (423 females, 74.0%) with established RA (11.8 years) were included. Disease activity indices were similar at baseline for females and males (swollen joints (28 joints) 3.1 vs 3.0, tender joints 4.3 vs 3.7, DAS28 5.83 vs 5.72). Females reported worse function (HAQ 1.64 vs 1.51 (P=0.037)) and more fatigue (6.7 vs 5.9, 0-10 scale (p=0.013)), but the same global score for disease activity as males (6.9 vs 6.8, 0-10 scale). No differences in disease activity measures or patient-reported outcomes developed, but females continued to report poorer function. The first biologic agents used were similar (etanercept 60.8% vs 61.1%; infliximab 20.3% vs 16.1%; adalimumab 17.0% versus 17.5%) as was retention on the first biologic agent (62.7% versus 70.5%, P=0.0866) with a median survival of 3.7 vs 3.3 years (logrank test p=0.25) (Figure 1 ). Frequency of switching and survival on subsequent biologics were the same. Image/graph: Conclusions: No sex differences were detected in drug retention and survival for patients requiring biologic therapy for RA. Females reported poorer function throughout the treatment course but disease activity measures were similar. Disclosure of Interest: None Declared